Studies on Compressive Strength Microstructural Analysis of Self-Compacting Mortar with Bacteria - Sravanthi, Middela; Venkateswara Rao, S.; Krishnaveni, Kanthala; Lal Meenuga, Venkata Kamal; Kariveda, Sujana (Communications - Scientific Letters of the University of Zilina, 2022)
This research proposed bacteria-treated concrete, which is highly desirable because the mineral precipitation induced from microbial activities is pollution free and natural. This study investigates the effects of Bacillus Licheniformis, Bacillus Cohnii and mixed bacteria on compressive strength, ultrasonic pulse velocity test, rapid chloride penetration test, microstructural analysis and bacteria cell concentration of 10 5cell/ml of normal and self-compacting mortars made with and without fly ash for 7 and 28 days. With self-compacting mortar, the compressive strength of Bacillus Licheniformis improved by 30.3 % and by adding Bacillus Cohnii in 28 days, the ion penetration value decreased. Finally, it was observed that the deposition of calcium carbonate in mortar improved compressive strength using SEM-EDS and XRD with compound polymorphisms of calcite, vaterite, quartz, and Hautirite.
Keywords: self-compacting mortar; compressive strength; bacillus licheninformis; bacteria cohnii; class-c fly ash; durability test